DINAMIKA VOLUME EKSPOR BIJI KOPI HIJAU INDONESIA: PERBANDINGAN DENGAN PASAR NEGARA KONSUMEN UTAMA - Pana Gelora; Denny Saputera (LPSDI Bina Patria, 2025)
Indonesia, with its diversity of coffee types and abundant production potential, has a great opportunity to dominate the world coffee market. Through data analysis of coffee consumption, global production, and import duty tariffs, this study shows that these three factors have a significant influence on Indonesia's coffee export volume. The high coffee consumption in destination countries is a great opportunity for Indonesia. However, to achieve market dominance, it is necessary to improve coffee bean quality, production capacity, and strengthen trade cooperation. This study shows that Indonesia needs to make several strategic efforts. First, improving the quality of coffee beans is essential. This can be achieved through the application of appropriate cultivation technology, good post-harvest processing, and quality certification. Second, increasing production capacity is also key. By increasing plantation area, productivity, and production efficiency, Indonesia can meet the growing market demand. Third, strengthening trade cooperation with destination countries is necessary. Through free trade agreements or trade preferences, Indonesia can improve market access and competitiveness of its coffee products. The results of this study provide important implications for the government, business actors, and coffee farmers. The government needs to provide greater support to the coffee sector, such as providing infrastructure, developing research and technology, and facilitating market access. Business actors need to continue to innovate and diversify their products to meet the increasingly diverse market needs. Meanwhile, coffee farmers need to improve their knowledge and skills in coffee cultivation and adapt to climate change.